2003
DOI: 10.1159/000072004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inhaled Corticosteroids with Different Lung Deposition on Exhaled Hydrogen Peroxide in Stable COPD Patients

Abstract: Background: The effects of inhaled corticosteroids (ICS) on markers of oxidative stress in patients with stable COPD are unclear. Objectives: The aim was to investigate the effect of ICS on exhaled H2O2 in stable COPD patients and to compare ICS with different lung deposition. Methods: Forty-one stable patients with moderate COPD (FEV1 ∼60% predicted) were randomized to sequence 1; first HFA-134a beclomethasone dipropionate (HFA-BDP, an ICS with more peripheral deposition) 400 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 17 publications
2
21
0
2
Order By: Relevance
“…21 In contrast, another study reported that ICSs reduced exhaled H 2 O 2 in subjects with stable COPD. 22 In our study, COPD subjects receiving ICS therapy had similar H 2 O 2 values, compared with steroid-naive subjects. According to this result, one might conceive that ICSs suppress inflammatory processes contributing to alleviation of oxidative stress.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…21 In contrast, another study reported that ICSs reduced exhaled H 2 O 2 in subjects with stable COPD. 22 In our study, COPD subjects receiving ICS therapy had similar H 2 O 2 values, compared with steroid-naive subjects. According to this result, one might conceive that ICSs suppress inflammatory processes contributing to alleviation of oxidative stress.…”
Section: Discussionsupporting
confidence: 55%
“…22 ICS or oral steroids significantly reduce the chemotactic activity of neutrophils and increase the neutrophil elastase inhibitory capacity in induced sputum. 23,24 In addition, evidence from in vitro studies suggests that among the anti-inflammatory actions of steroids there is a reduction in the generation of ROS by neutrophils.…”
Section: Discussionmentioning
confidence: 93%
“…In COPD patients with exacerbations, higher levels of expired H 2 O 2 were found than in patients in stable condition [45]. Inhaled steroids had no effect on H 2 O 2 level in this disease in some studies [45,74], but caused a decrease in another investigation [89]. Long-term antioxidant treatment with N-acetylcysteine decreased exhaled H 2 O 2 concentration in patients with COPD [75].…”
Section: Diseases States That Influence H 2 Omentioning
confidence: 92%
“…Biopsy studies showed a reduction in the number of mast cells by ICS [32]. Treatment with ICS reduces the concentration of exhaled NO [33] and H 2 O 2 [34] in exhaled air. Recent placebo-controlled trials show no effect of prolonged treatment on the course of forced expiratory volume in one second (FEV1) in mild COPD [35][36][37][38].…”
Section: Pharmacotherapy Of Copdmentioning
confidence: 97%